2020
DOI: 10.1108/ijssp-06-2019-0108
|View full text |Cite
|
Sign up to set email alerts
|

How long is a parental leave and for whom? An analysis of methodological and policy dimensions of leave length and division in Sweden

Abstract: Purpose Parental leave in Sweden can be taken both as paid and unpaid leave and often parents mix these forms in a very flexible way. Therefore, multiple methodological issues arise regarding how to most accurately measure leave length. The purpose of this paper is to review the somewhat complex legislation and the possible ways of using parental leave before presenting a successful attempt of a more precise way of measuring leave l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
(28 reference statements)
1
19
0
Order By: Relevance
“…Education background now appears highly influential, fathers with the longest educations now taking the most leave days, and the least-educated fathers taking the fewest: Those with only lower-secondary schooling take on average approximately 26 days leave, compared to 56 days in couples where fathers have a master's degree. Other studies of parental leave among fathers document the same pattern (e.g., Duvander, 2014;Duvander & Viklund, 2019). The figure also shows a combined effect of mother's education and father's leave take-up; male partners of highly educated women take longer leave, perhaps because the mother in this case prefers to share the leave and return to work sooner.…”
Section: Parental Leave Take-up: the Gender And Education Gradientsupporting
confidence: 53%
See 1 more Smart Citation
“…Education background now appears highly influential, fathers with the longest educations now taking the most leave days, and the least-educated fathers taking the fewest: Those with only lower-secondary schooling take on average approximately 26 days leave, compared to 56 days in couples where fathers have a master's degree. Other studies of parental leave among fathers document the same pattern (e.g., Duvander, 2014;Duvander & Viklund, 2019). The figure also shows a combined effect of mother's education and father's leave take-up; male partners of highly educated women take longer leave, perhaps because the mother in this case prefers to share the leave and return to work sooner.…”
Section: Parental Leave Take-up: the Gender And Education Gradientsupporting
confidence: 53%
“…Parental leave take-up being closely associated with education levels is often seen as a matter of different gender values. In fact, parents' education is often used to indirectly measure norms and attitudes toward gender equality, with higher education likely being associated with more gender-equal norms, which drives leave take-up (Duvander & Viklund, 2019). As shown in the section on gender attitudes, however, there is no such apparent association between education and gender equality attitudes in Denmark.…”
Section: Parental Leave Take-up: the Gender And Education Gradientmentioning
confidence: 99%
“…For the largest share of parental leave, the benefits received by parents reaches approximately 80% of the previous income, until a certain ceiling. There is significant flexibility in how to share and allocate the leave periods (Duvander and Viklund 2020). In 2010, parental leave could be used anytime up to the child turned 8 years old and it was commonplace to use leave over different periods.…”
Section: Methodsmentioning
confidence: 99%
“…It is found that parents' labor market statuses, education and income levels, as well as the father's share of income, are important for parental leave use [13,23,32,33]. The relationship between leave and fathers' income seems to be curvilinear, as the fathers with the highest incomes do not use the most leave.…”
Section: When Do Fathers Use Parental Leave?mentioning
confidence: 98%